Influence of nutrient and light management on postharvest quality of lettuce (Lactuca sativa L.) in soilless production systems. - Mandizvidza, Tonderai Clive (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.